Trauma and Identity; Traumatic Otherness in Gharbi Mustafa's “What Comes with the Dust” - Muli Amaye; Yadgar Ismail Said (Zanco Journal of Human Sciences, 2026)
The paper explores Gharbi Mustafa’s novel, What Comes with the Dust (2018), which portrays the status of Kurdish Yezidis who were targeted as a religious minority. The text reflects on the social and political life in the disputed Kurdistani territories that have been previously Arabized let alone political attempts to separate them from the Kurds. They have faced many operations from the surrounding entities and were always treated as others; devalued and marginalized people. Their villages, and history were targeted in addition to denying their political, religious, and cultural rights. The suffering of the Yezidis, more specifically the female characters, is to a great degree a traumatic experience where they feel disvalued and marginalized. The novel showcases the regressive, radical, inhumane treatment the Yezidi female characters faced under ISIS and by people under ISIS. The Kurdish Yezidis, as a religious minority were left unprotected after the Iraqi army’s destruction in the disputed territories. This resulted in distrust and led to thousands of casualties, the enslavement of women and children, the mass murder of the males, and the destruction of their houses. The novel portrays characters that were stuck in a harsh reality as they were targeted due to their religious and ethnic identities in post-colonial Middle East. The novel will be analyzed through postcolonial otherness and trauma theories to find out how such experienced affected their identities.